Gramatyka a granice wyrażalności w pismach mistyków kościoła katolickiego = Grammar and borders of ineffability in the scriptures of Polish catholic mystics - Rutkowska, Izabela (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The object of considerations undertaken in the article is the anthology of texts written by Polish catholic mystics ("Antologia mistyki polskiej II", edited by Marian Zawada OCD). This work aims to indicate the most critical problems with the grammatical forms exploited to describe the mystical, supernatural experiences, which are known as the ineffable phenomena. Mystics write about these problems in the metalingual comments. They regret the human language, too weak to express the richness of the world of their souls.
Keywords: niewyrażalność; gramatyka; polskie teksty mistyczne; lingwistyka; teolingwistyka; chrześcijaństwo; ineffability; grammar; Polish mystical texts; linguistics; theolinguistics; Christianity